2006 International Conference on Machine Learning and Cybernetics 2006
DOI: 10.1109/icmlc.2006.258757
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the System's Hierarchical Structure Through Integration of Dematel and ISM

Abstract: To ensure the hierarchical structure of complex system illustrative and reasonable, the new method is presented to build and adjust hierarchical structure of complex system through integration of Decision Making Trial and Evaluation Laboratory (DEMATEL) and Interpretive Structural Modeling (ISM) models. First of all, the rationale and procedures of integrating DEMATEL and ISM are analyzed; then the method to perfect system's hierarchical structure with dummy nodes is proposed, which can be viewed as the images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…ISM and DEMATEL are complementing and powerful structural modeling techniques and deemed superior to other interpretive and decision modeling techniques [72], [73]. Integrated ISM-DEMATEL has been successfully utilized in various contexts and in various fields to deal with decision-making problems [72], [74]- [76]. However, limited use of ISM-DEMATEL combination has been undertaken by studies in the software engineering domain, therefore studies using these methodologies separately are discussed.…”
Section: B Existing Models/framework Using Interpretive Structural Modeling (Ism) and Decision-making Trial And Evaluation Laboratory (Dementioning
confidence: 99%
“…ISM and DEMATEL are complementing and powerful structural modeling techniques and deemed superior to other interpretive and decision modeling techniques [72], [73]. Integrated ISM-DEMATEL has been successfully utilized in various contexts and in various fields to deal with decision-making problems [72], [74]- [76]. However, limited use of ISM-DEMATEL combination has been undertaken by studies in the software engineering domain, therefore studies using these methodologies separately are discussed.…”
Section: B Existing Models/framework Using Interpretive Structural Modeling (Ism) and Decision-making Trial And Evaluation Laboratory (Dementioning
confidence: 99%
“…If 1 or more number falls at the same level, this technique is unable to justify the importance of the elements within that level. Hence, an integrated approach of DEMATEL and ISM has been suggested by 55 and found useful to get the detailed analysis of all the elements involve in a system. 53,54 As DEMATEL technique facilitates to find out the magnitude of the relational impact of the factors, it considers all the direct and indirect effects to find the strength of relations, but it is unable to categorize the level of the elements.…”
Section: Interpretive Structural Modelingmentioning
confidence: 99%
“…53,54 As DEMATEL technique facilitates to find out the magnitude of the relational impact of the factors, it considers all the direct and indirect effects to find the strength of relations, but it is unable to categorize the level of the elements. 51,55 Considering DEMATEL and ISM methods as structural modeling techniques, Yin et al 51 have explained the usefulness of their integration and found these techniques complementary to each other for the logical, systematic, and the directional level-wise causal relationship of the system elements. 56 Interpretive structural modeling methodology offers the binary choice as 0 and 1 for assessment, while DEMATEL provides more options (0, 1, 2, 3) to get into detail.…”
Section: Interpretive Structural Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1: Zhou et al (2006) found that total-relation matrix T in DEMATEL and reachability matrix K in ISM has something in common. This study set up a threshold.…”
Section: Hierarchical Structure Analysis Of Randd Alliance Ksfmentioning
confidence: 99%